A transcription co-factor integrates cell adhesion and motility with the p53 response. - Coutts, A; Weston, L; La Thangue, N (2009)
Despite its obvious importance in tumorigenesis, little information is available on the mechanisms that integrate cell motility and adhesion with nuclear events. JMY is a transcription co-factor that regulates the p53 response. In addition, JMY contains a series of WH2 domains that facilitate in vitro actin nucleation. We show here that the ability of JMY to influence cell motility is dependent, in part, on its control of cadherin expression as well as the WH2 domains. In DNA damage conditions JMY undergoes nuclear accumulation, which drives the p53 transcription response but reduces its influence on cell motility. Consequently, the role of JMY in actin nucleation is less in damaged cells, although the WH2 domains remain functional in the nucleus where they impact on p53 activity. Together, these findings demonstrate a pathway that links the cytoskeleton with the p53 response, and further suggest that the ability of JMY to regulate actin and cadherin is instrumental in coordinating cell motility with the p53 response.